If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(1 + 3b) = -20 + 3b (1 * 10 + 3b * 10) = -20 + 3b (10 + 30b) = -20 + 3b Solving 10 + 30b = -20 + 3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3b' to each side of the equation. 10 + 30b + -3b = -20 + 3b + -3b Combine like terms: 30b + -3b = 27b 10 + 27b = -20 + 3b + -3b Combine like terms: 3b + -3b = 0 10 + 27b = -20 + 0 10 + 27b = -20 Add '-10' to each side of the equation. 10 + -10 + 27b = -20 + -10 Combine like terms: 10 + -10 = 0 0 + 27b = -20 + -10 27b = -20 + -10 Combine like terms: -20 + -10 = -30 27b = -30 Divide each side by '27'. b = -1.111111111 Simplifying b = -1.111111111
| 15=(2.5x)/2 | | 5.7+0.8x=0.9 | | (-5.5)-(-8.7)= | | 3(4x-2.4)=5x-7.2 | | 20/2(5*5)=x | | 2k^2+6=4k | | (-3.8)+(0.13)= | | 3y/5=37-4 | | 4.7+0.05x=5.09 | | 7.1=10x+1.5 | | Ln(x-1)+Ln(3)=Lnx | | (x+1)+(x-1)=45 | | f=4.135135 | | 10log(1/4) | | -0.1(4x+1)-3.5x= | | 3m+(m-10)=180 | | 5*2x=40 | | 3+(9+3)=-3(-3*-24) | | x^2+6x+18=12 | | 5y+6=3y-9 | | h=-1.7t^2+3.5 | | 13x-81+92=360 | | x^2+6x+6=12 | | 50*20m=10+30m | | -13=5(1+4a)-2a | | y=1/2(x-4)^2-32 | | 2x^2+13x-1=0 | | 3x^2-2=x-3 | | 7a-14/-4 | | 2.5X-23X= | | 42=8a+13a | | (x)(x+1)(x+2)(x+3)=5334 |